ИННОВАЦИИ КАК НАПРАВЛЕНИЕ ГОСУДАРСТВЕННОЙ СТРАТЕГИИ РАЗВИТИЯ РЕСПУБЛИКИ КАЗАХСТАН - Баимбетова, А А (Journal of Economic Research & Business Administration, 2015)
In given article directions of innovative activity, theoretical and practical level of innovative activity of Republic of Kazakhstan are considered. Also innovative projects of the state scale and realised innovative business projects are considered.